The Recent Hate Campaigns whether impacted the Community Relationship between Buddhists and Muslims in Sri Lanka? - Razick, Ahamed Sarjoon; Gafoordeen, N.; Long, Ahmad Sunawari; Salleh, Kamarudin (My University, 2017)
Sri Lanka is a diverse country and is home to many religions, ethnicities, and languages. Sinhala-Buddhists are the predominant ethnic group in this country, constituting 70.19% of the total population, with the Muslims being the second largest minority. There are a wealth of records in history that prove the cordial relationship between Buddhists and Muslims in the past. However, the aftermath of civil war (1983-2009) caused tension to brew between these two groups. This is because of recent hate campaigns undertaken by a number of Buddhist Nationalist Groups (BNGs) through instigation of Buddhism or Sinhalese nationalism among Buddhists adherents. These groups have been actively protesting against the Muslim social, cultural, and religious practices and behaviours, such as the issuing of Halal certification, slaughtering of animals for food, conducting of prayer services, maintaining worship places, etc. They have also disseminated misinterpretations about Muslims and their religion, Islam, spreading derogatory speeches among the Buddhists. Given the above background, this paper has attempted to determine the impacts of recent campaigns on the traditional relationship between Buddhists and Muslims via an analysis of Buddhist and Muslim point of views. According to the Buddhists, the recent attempts instigated by Buddhist Nationalist Groups have not impacted their relationship with the Muslims in any way and that they still habitually maintain a cordial relationship with said community. Even the Muslims feel as strongly in terms of keeping a cordial relationship with the Buddhists. However, according to their point of view, these hate campaigns could potentially ruin their already harmonious relationship with the Buddhists, turning it into a conflicting relationship instead. Therefore, both the Buddhist and Muslim communities in Sri Lanka plan to be more vigilant against these harmful campaigns.
Keywords: recent tension, community relationship, Muslims, Buddhists, Sri Lanka